Quantitative trait loci analysis of mineral element concentrations in an Arabidopsis halleri x Arabidopsis lyrata petraea F2 progeny grown on cadmium-contaminated soil - Willems, Glenda (The New phytologist, 2010)
SUMMARY: This study describes the quantitative trait locus (QTL) analysis of cadmium (Cd), zinc (Zn), iron (Fe), potassium (K), magnesium (Mg) and calcium (Ca) accumulation in the pseudometallophyte Arabidopsis halleri under conditions of Cd excess using an interspecific A. halleri x Arabidopsis lyrata F(2) population. *Our data provide evidence for the implication of one major QTL in Cd hyperaccumulation in A. halleri, and suggests that Cd tolerance and accumulation are not independent in A. halleri. Moreover, the major loci responsible for Zn hyperaccumulation in the absence of Cd appear to be the same when Cd is present at high concentrations. *More than twofold higher Fe concentrations were measured in A. halleri shoots than in A. lyrata, suggesting a different regulation of Fe accumulation in the hyperaccumulator. *With the exception of Ca, the accumulation of Cd was significantly correlated with the accumulation of all elements measured in the F(2) progeny, suggesting pleiotropic gene action. However, QTL analysis identified pleiotropic QTLs only for Cd, Zn and Fe. Mg accumulation was negatively correlated with Cd accumulation, as well as with dry shoot biomass, suggesting that it might indicate cellular damage